Investigational drugs for anxiety in patients with schizophrenia. (April 2015) - Garay, Ricardo P; Samalin, Ludovic; Hameg, Ahcène; Llorca, Pierre-Michel
<x xml:space="preserve">Abstract</x> Introduction: Anxiety is a frequent symptom of schizophrenia, which is highly associated with an increased risk of relapse and suicide. The effect of antipsychotics on this clinical dimension is not specific and the common practice of prescribing benzodiazepines remains unsatisfactory. Areas covered: The authors review recent well-designed clinical trials for anxiety in patients with schizophrenia. The content includes information derived from trial databases, regulatory authorities and scientific literature. Expert opinion: Anxiety in schizophrenia has severe consequences and specific clinical features, which require a specific therapy, beyond benzodiazepines. In these past 2 years, two compounds (the anticonvulsant/anxiolytic pregabalin and the atypical antipsychotic quetiapine) were on Phase III/IV clinical trials for schizophrenia, with comorbid anxiety as a primary outcome measure. Potential for success is high, given their strong rationale and the clinical experience with both drugs. Anxiety (as a symptom) was a secondary outcome measure in trials for schizophrenia involving seven other compounds (lurasidone, amisulpride, bitopertin, oxytocin, famotidine, cannabidiol and the L-theanine and pregnenolone combination). Primary completion date is expected in the next 2 years. In spite of ancient positive results and a strong rationale, aripiprazole and related compounds were not in recent clinical trials. The authors believe that these compounds deserve more attention.